Aqua Fitness as one of the methods of prevention of hip osteoarthritis - Bartłomiej Wrzesiński; Edyta Piechocka; Anna Karpińska; Patrycja Łopatka; Paweł Wojtczak; Anna Ziółkowska (Kazimierz Wielki University, 2018)
Aqua fitness training is one of the most effective methods for improving physical health and reducing pain in orthopedic patients. This training due to the extensive number of modules can be used at any age regardless of gender. Aquafitness due to the environment in which it takes place gives great effects in the treatment of osteoarthritis, especially in combination with other physiotherapeutic treatments and kinesitherapy.